The Bone Marrow Functions as the Central Site of Proliferation for Long-Lived NK Cells - van Helden, Mary J.G. (2012)
NK cells play an important role in the early defense against invading pathogens. Although it is well-established that infection leads to a substantial, local increase in NK cell numbers, little is known about the mechanisms that trigger their proliferation and migration. We here investigated the dynamics of NK cell responses following intranasal respiratory virus infection. We show that NK cell numbers increased in the airways following influenza virus infection, but find no evidence of proliferation either at the site of infection or in the draining lymph nodes. Instead, we find that the bone marrow (BM) is the primary site of proliferation of both immature and mature NK cells during infection. Using an adoptive transfer model, we demonstrate that peripheral, long-lived and phenotypically mature NK cells migrate back to the BM and proliferate there, both homeostatically and in response to infection. Thus, the BM is not only a site of NK cell development, but also an important site for proliferation of long-lived mature NK cells.